Rainfall shocks, per capita income and rural out-migration - Nathan Delacrétaz; Bruno Lanz; Amir H. Delju; Étienne Piguet (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
Rural regions are more exposed to rainfall shocks, notably through agriculture, and understanding how local population adapt to changes in the climate is an important policy challenge. In this paper we exploit longitudinal data for Turkish provinces from 2008 to 2018 together with precipitation records over more than 30 years to study how shocks to 12-month standard precipitation index (SPI) affect out-migration across rural, transitional and urban regions, and we document how these impacts are channeled through local income, agricultural GDP, and conflicts. Based on fixed effect regressions controlling for unobserved heterogeneity across provinces and over time, we find evidence that negative SPI shocks are associated with higher out-migration in rural provinces. We also show that the relationship is fully mediated by per capita GDP, whereas agricultural GDP and conflicts do not play a role.
Keywords: 330; out-migration; climate change; rainfall; urbanization; per capita income; agriculture; conflicts